PENGALAMAN BERORGANISASI DALAM MEMBENTUK SOFT SKILL MAHASISWA - Suranto Suranto; Famila Rusdianti (Jurnal Pendidikan Ilmu Sosial, 2018)
The purposes of this study are to determine what factors affect the students of the Faculty of Teacher Training and Education (FKIP) Muhammadiyah University of Surakarta and to find out how important the experience of organizing in forming soft skill student. The type of this research is qualitative research with ethnography method. The subject of this research are students of Accounting Education Faculty of Teacher Training and Education UMS. The results of this study claimed the organization’s experience can develop the students’ soft skills, advantages acquired in organization that are developing leadership skill, communication skill, teamwork, networking, problem solving, and managing conflict. This results claimed that three intrinsic factors consisted of interest, talent, and perception. The factor of perception becomes fundamental’s factor is to influence students to join the organization. The students have a viewpoint that the organization activities can develop and improve the students’ soft skills.